Creep Properties of a Viscoelastic 3D Printed Sierpinski Carpet-Based Fractal - Juan B. Pascual-Francisco; Orlando Susarrey-Huerta; Leonardo I. Farfan-Cabrera; Rockali Flores-Hernández (Fractal and Fractional, 2023)
In this paper, the phenomenon of creep compliance and the creep Poisson’s ratio of a 3D-printed Sierpinski carpet-based fractal and its bulk material (flexible resin Resione F69) was experimentally investigated, as well as the quantification of the change in the viscoelastic parameters of the material due to the fractal structure. The samples were manufactured via a vat photopolymerization method. The fractal structure of the samples was based on the Sierpinski carpet at the fourth iteration. In order to evaluate the response of both the fractal and the bulk material under the creep phenomenon, 1 h-duration tensile creep tests at three constant temperatures (20, 30 and 40 °C) and three constant stresses (0.1, 0.2 and 0.3 MPa) were conducted. A digital image correlation (DIC) technique was implemented for strain measurement in axial and transverse directions. From the results obtained, the linear viscoelastic behavior regime of the fractal and the bulk material was identified. The linear viscoelastic parameters of both fractal and bulk materials were then estimated by fitting the creep Burgers model to the experimental data to determine the effect of the fractal geometry on the viscoelastic properties of the samples. Overall, it was found that the reduction in stiffness induced by the fractal porosity caused a more viscous behavior of the material and a reduction in its creep Poisson’s ratio, which means an increase in the compliance of the material.